Remodeling of distal radius fractures in children: preliminary retrospective cost/analysis in level II pediatric trauma center - Marinelli, Mario; Massetti, Daniele; Facco, Giulia; Falcioni, Danya; Coppa, Valentino; Maestri, Valentina; Gigante, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Children displaced distal radius fractures (DRFs) are commonly treated by reduction. Yet, their excellent remodeling ability provides good clinical-radiographic outcomes even in case of non-anatomical reduction. The reduction under analgesia or sedation involves hospitalizations, greater risks, and higher hospital costs. The aim of this preliminary study is to demonstrate the accountability and conveniency of non-anatomical reduction.Methods: The study involved all 0-8 years-old children who were affected by a closed overriding DRF from February 2017 to December 2018 and were managed non-operatively by a long arm cast without reduction, analgesia, or sedation treatments. We retrospectively evaluated their clinical-radiographic outcomes and healing time. The costs of no-reduction treatments were compared with those of the two main approaches to DRFs, that is: closed reduction under sedation and application of a long arm cast; closed reduction under anesthesia, percutaneous pinning, and application of a long arm cast. The comparison was based on the Diagnosis Related Group system.Results: We treated 11 children with an average initial radial shortening of 5±3 mm and average initial sagittal and coronal angulations of 4.0° and 3.5°, respectively. Average casting duration was 40 days. All patients achieved a full range of wrist motion without deformities. The procedure was respectively 7 times less expensive than closed reduction in emergency room under sedation and application of a long arm cast, and 64 times less expensive than closed reduction in the operating room under anesthesia, percutaneous pinning, and application of a long arm cast.Conclusions: In children aged 0-8 years, non-operative treatment of closed overriding DRFs with a long arm cast without reduction is a simple and cost-effective procedure with both clinical and radiographic medium-term excellent outcomes.